The Influence of Online Game Intensity on Students' Tahfidz Achievement - Rahmadania, Nanda Putri Izza; Suprihno, Suprihno; Suripto, Suripto (Faculty of Education and Teacher Training of UINSI Samarinda, 2023)
This research focuses on examining the influence of the intensity of tahfidz students in engaging with online games on student achievement within the tahfidz program at the Islamic Elementary School level in Tulungagung Regency. This research constituted an ex post facto quantitative investigation to elucidate the interrelationship among variables. The study population comprised students from several Islamic elementary schools participating in the Tahfidz program, totalling 143 students. The sampling technique employed was non-probability sampling, specifically purposive sampling. The research sample consisted of fifth- and sixth-grade tahfidz students who played online games for more than one hour per day, which amounted to 113 students. This study collected data based on the pure value of students' tahfidz proficiency as stated in their semester one report card. The outcomes of this research demonstrate that the extent of engagement in online gaming significantly impacts the tahfidz achievement of students by 37.9%, with a significance value (sig.) derived from the coefficient table at 0.001 < 0.05. This suggests that the variable of online gaming (X) exerts a significant influence on the tahfidz performance of students (Y). Based on the research findings, the intensity of playing online games can be a significant factor in determining the achievement of tahfidz students in Islamic elementary schools, thus necessitating further supervision from parents and educators. The study results imply the importance of a comprehensive and collaborative approach in addressing the negative impacts of the digital era, including the intensity of playing online games, by involving various stakeholders such as educators and parents, thereby supporting students to develop holistically.